The oral-gut microbiome axis in breast cancer: from basic research to therapeutic applications - Huang, Lan; Jiang, Chun; Yan, Meina; Wan, Weimin; Li, Shuxiang; Xiang, Ze; Wu, Jian (Frontiers in Cellular and Infection Microbiology, 2024)
As a complicated and heterogeneous condition, breast cancer (BC) has posed a tremendous public health challenge across the world. Recent studies have uncovered the crucial effect of human microbiota on various perspectives of health and disease, which include cancer. The oral-gut microbiome axis, particularly, have been implicated in the occurrence and development of colorectal cancer through their intricate interactions with host immune system and modulation of systemic inflammation. However, the research concerning the impact of oral-gut microbiome axis on BC remains scarce. This study focused on comprehensively reviewing and summarizing the latest ideas about the potential bidirectional relation of the gut with oral microbiota in BC, emphasizing their potential impact on tumorigenesis, treatment response, and overall patient outcomes. This review can reveal the prospect of tumor microecology and propose a novel viewpoint that the oral-gut microbiome axis can be a breakthrough point in future BC studies.